2018
DOI: 10.1038/s41556-018-0216-y
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic islet-autonomous insulin and smoothened-mediated signalling modulate identity changes of glucagon+ α-cells

Abstract: The mechanisms restricting regeneration and maintaining cell identity following injury are poorly characterized in higher vertebrates. Upon β-cell loss, 1–2% of the glucagon-producing α-cells spontaneously engage in insulin production in mice. Here we explore the mechanisms inhibiting α-cell plasticity. We show that the adaptive α-cell identity changes are constrained by intra-islet Insulin- and Smoothened-mediated signaling, among others. The combination of β-cell loss, or insulin signaling inhibition, with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
69
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 50 publications
11
69
1
Order By: Relevance
“…In these mice, the DTR is specifically overexpressed on the surface of the β‐cells, under the control of the RIP. As previously described, upon diphtheria toxin (DT) administration, the β‐cell compartment is specifically ablated with extremely high and reproducible efficiency (97.88% in NSG RIP‐DTR, Figure B,C), similar to the one reported for SCID RIP‐DTR (97.8%) . Ablated animals developed hyperglycaemia and displayed lower weight compared to their normoglycaemic counterparts (Figure D,E).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…In these mice, the DTR is specifically overexpressed on the surface of the β‐cells, under the control of the RIP. As previously described, upon diphtheria toxin (DT) administration, the β‐cell compartment is specifically ablated with extremely high and reproducible efficiency (97.88% in NSG RIP‐DTR, Figure B,C), similar to the one reported for SCID RIP‐DTR (97.8%) . Ablated animals developed hyperglycaemia and displayed lower weight compared to their normoglycaemic counterparts (Figure D,E).…”
Section: Resultssupporting
confidence: 71%
“…The mice were given ad libitum access to water and standard diet RM1A (SDS). First group received three intraperitoneally (ip) DT (Sigma, cat.# D0564‐1MG) injections to induce diabetes as previously described . Blood glucose was monitored twice a week at 4‐5 pm with a Contour XT glucometer (Bayer) to confirm diabetes (blood glucose >300 mg/dL on 2 consecutive measurements).…”
Section: Methodsmentioning
confidence: 99%
“…Their identification as regeneration modulators through gene profiling analyses will be cumbersome. As mentioned above, we have found, for instance, that insulin and hedgehog signaling in pancreatic islets are such players …”
Section: Resultsmentioning
confidence: 63%
“…Hence, Hedgehog and Insulin signaling are, together with other pathways not yet identified, natural brakes making α-cells to preserve their identity. 102 By using a wide range of genetic tools, recent studies have revealed that α-to-β transdifferentiation can be artificially potentiated by the concomitant inhibition of the key α-cell-specific transcription factor Arx and the epigenetic modifier DNMT1. 103 This suggests that α-cells are epigenetically locked, and that these brakes can be released.…”
Section: Pancreasmentioning
confidence: 99%
See 1 more Smart Citation